Peran Brand Image Memediasi Pengaruh Word of Mouth (WOM) Terhadap Niat Beli Konsumen Studi Kasus pada Kedai Kopi Aghara - Jon Edy; Sri Winda Hardiyanti Damanik; Karina Rizky Nur Ramadhani (Teewan Journal Solutions, 2025)
This study aims to find the role of brand image in mediating the influence of word of mouth on purchase intention in Kedai Kopi Daycoff The research is explanatory research which describes causal relation among variables with hypothesis test. This study use 91 respondents as sample. The research uses slovin formula to find the sample. This study use instrument test and path analysis. Based on test results can be summarized that word of mouth has effect and significantly on purchase intention, word of mouth has not effect and not significantly on brand image, and brand image has effect and significantly on purchase intention. The result also shows thatword of mouth has not effect and noot significantly on purchase intention through brand image